Evolution of female characters of the sanskrit epic mahabharata in cinematography - Sabirova, Rimma (2018)
The article deals with the problem of the ancient Indian epic "Mahabharata" female characters and their evolution in cinematography. The issues, covered in the work, are more essential now than ever and demand thorough research. In the time of emancipation and the global gender "equality", the women's question is a vexed point. The object of study is the ancient Indian epic Mahabharata in Indian literature and cinema, namely the 1965 film and TV series of 1988 and 2013. The subject of the study is the epic images of women in Indian cinema. Using the comparative approach, the analysis of women's images of cinema and epic is presented; their transformation in modern cinema is examined. Watching these movies one can clearly follow the trend of changing attitudes and drawing attention to the urgent problems of Indian women: position in society, upbringing, education, freedom, family relationships, confirming the relevance of the chosen topic. Screen versions of Sanskrit epics combine tradition and innovation; moreover every new screen version makes the women's issue more acute due to the transformation of female characters.